Operational Efficiency Study Of The Effeciency Of Ammonium Nitrate Loading And Unloading Operations At Pt Kutai Jaya Pundinusa Bontang: Ammonium Nitrate - lia, Rakhel; Indrawati; Fabiola Bulimasena Luturmas; Yolastasya Br Sembiring; Sang Ayu Made R (Manajemen Pendidikan Program Doktor, 2025)
This study evaluates the operational efficiency and safety of Ammonium Nitrate loading and unloading at PT Kutai Jaya Pundinusa, Bontang, East Kalimantan. Given the material's hazardous nature, the research focuses on operational factors, including time efficiency, equipment capacity, workforce performance, and adherence to workplace safety standards. Using field observations, interviews, and qualitative data analysis, the study seeks to identify effectiveness hindrances and provide actionable recommendations. Its contribution lies in enhancing maritime supply chain management for hazardous materials, improving logistical efficiency, and strengthening safety protocols at industrial ports.